The lore of the Mandarins : towards a non-partisan public service in Bangladesh - Shawkat Ali, A. M. M. (Dhaka : University Press, 2002)
On the services of the Bangladesh Public Service Commission.
Includes bibliographical references (pages [301]-306) and index.
Donated By Akbar Ali Khan
Keywords: Civil service -- Bangladesh; Public administration -- Bangladesh